A Systemic Review on Topical Marketed Formulations, Natural Products, and Oral Supplements to Prevent Androgenic Alopecia: A Review - Sumel Ashique; Navjot Kaur Sandhu; Sk. Niyamul Haque; Kartick Koley (Natural Products and Bioprospecting, 2020)
Abstract Androgens have an intense consequence on the human scalp and body hair. Scalp hair sprouts fundamentally in awol of androgens whereas the body hair hike is vulnerable to the activity of androgens. Androgenetic alopecia (AGA) invoked as males emulate Alopecia due to the cause of the dynamic reduction of scalp hair. Androgens are medium of terminus growth of hair although the body. Local and system androgens convert the extensive terminal follicles into lesser vellus like structure. The out start of this type of alopecia is intensely irregular and the reason behind this existence of enough circulating steroidal hormones androgens and due to genetic predisposition. Effective treatments are available in the market as well as under clinical and preclinical testing. Many herbal formulations are also available but not FDA approved. Different conventional and NDDS formulations are already available in the market. To avoid various systemic side effects of both Finasteride and Minoxidil, topical formulations and natural products (nutrients, minerals, vitamins) now a days are being widely used to treat Androgenic alopecia. CAM (complementary and alternative medicine) provides the option to elect favorable, low-risk, adjuvant and alternative therapies. Herein, we offer a widespread review of topical marketed formulations, natural products, and CAM treatment options for AGA. Graphic Abstract